Política pública de cota racial de inclusão do negro no serviço público: uma análise da implementação em uma Universidade Pública Federal - Soares Junior, Miguel Freitas (2023)
The objective of this study is to analyze the implementation of the racial quota public policy - Law No. 12,990/2014 - within the Federal University of Paraiba (UFPB), for the entry of administrative technical servers, in the light of the qualitative approach in the socio-historical perspective of configuration of the problem posed. As for the procedures for collecting and analyzing material, the techniques of document analysis and thematic content analysis were applied to the documents configuring the implementation of the public policy at UFPB, as well as to the generating documents of the referred public policy: the Brazilian Constitution of 1988 and Law No. 12,990/2014. The Results and Discussion were presented following the three documentary references: 1. the Brazilian Constitution of 1988, including the Preamble and articles 1, 3, 5, 6, 7, 37, 170, 193, 214, 215 and 227, which deal with issues related to black people and racism. 2. law 12.990/2014. 3. UFPB documents implementing the public policy of racial quota for the inclusion of blacks in public service. In the first document reference, the following thematic axes were identified: Social Justice as a tool to combat inequality: Labor as a social right, Dignity of the human person, free from prejudice. Such axes reveal the content of the search for justice, equality and dignity. In the second documental reference, the thematic axes were evidenced: The reservation and guarantee of vacancy, Affirmation of black identity. Public policy and equity axes which highlight the responsibility of public policy as a real instrument to combat racism, In the third set of documental references, documents produced by UFPB, we identified the tracks/themes that the University, as a manager, has presented in the process of implementing this policy: UFPB-Structure, Processes and Public Policy for racial quotas for entry into public service UFPB Institutional Development Plan and racial quotas for entry into public service: UFPB - Public competitions for administrative technicians, edicts and racial quotas. As for the proposals for intervention, the following were suggested the forecasting of a percentage of racial quotas in the PDI for hiring new public servants: the restructuring of PROGEP's Commission for Hetero-identification and the creation of an exclusive sector for planning support consultation, and monitoring of the implementation of public policy. The implementation is the realization of the policy through which those contemplated benefit from opportunities, reaching the reality of entering the federal public service. The research raised some weaknesses in the implementation of public policy, within the UFPB, related these weaknesses with other studies that dealt with the same subject and proposed points of improvement capable of contributing to the management of the implementation of public policy in the context of the University, considering the indicatives of the organizational reality pointed out by the study.